The impact of covid-19 on residential preference in Klang valley - Hwan, Tiong Piow (2023)
Since the outbreak of COVID-19 in Malaysia, the government of Malaysia has implemented series of movement restriction control to prevent the collapse of healthcare systems due to the increase of daily infection cases in Malaysia. During the COVID-19 outbreak, property market performance was greatly affected and shown a significant decline in year 2020 compared to 2019 according to NAPIC’s record. There are studies reveal that the impact of COVID-19 pandemic has changed the human’s living style include living lifestyle, work, and entertainment. Behaviour across social demographic could be different after COVID-19 outbreak, moreover if the impact has affected on the homebuyers’ financial status. In this situation, further studies shall be conducted to examine whether the homebuyers’ preference has changed after COVID-19 outbreak. Therefore, the purpose of this study is to identify homebuyers’ preference after the outbreak of COVID-19 and examine the difference in housing preference across homebuyers’ socio-demographic characteristics. For this study, 386 data were collected through online survey platform ‘Microsoft Form’ which distributed between January 2023 to February 2023. However, 374 sample were used to analyse in this study. ‘Descriptive analysis’ and ‘Mann-Whitney-U test’ were adopted to determine the significant of the housing attributes and compare to the findings from the literature review. Differential in housing preference before and after the outbreak of COVID-19 will be identified and explained by supporting studies. Any shortfall in supporting study would be the research gap in future. In summary, this study provides a better understanding of the residential preferences impact after COVID-19 outbreak for market players.